<htm>Phytohyperaccumulator-AMF (arbuscularmycorrhizal fungi) interaction in heavy metals detoxification of soil </htm> - Umar, Aisha (Acta Biológica Paranaense, 2017)
<htm>Phytohyperaccumulator-AMF (arbuscularmycorrhizal fungi) interaction in heavy metals detoxification of soil </htm>